2020
DOI: 10.7150/jca.35426
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CDK9 expression within chordoma tissues and the therapeutic potential of a selective CDK9 inhibitor LDC000067

Abstract: Objectives: Chordomas are slow-growing malignancies that commonly affect vital neurological structures. These neoplasms are highly resistant to current chemotherapeutic regimens and often recur after surgical intervention. Therefore, there is an urgent need to identify molecular targets and more robust drugs to improve chordoma patient outcomes. It is well accepted that cyclin-dependent protein kinase 9 (CDK9) has tumorigenic roles in various cancers; however, the expression and significance of CDK9 in chordom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…The tissue microarray (TMA) was constructed from 55 individual chordoma patient specimens within a formalin-fixed paraffin-embedded (FFPE) block as previously described. 23,24 The clinicopathological characteristics of the specimens were collected and are outlined in Table 1, including age, gender, tumour location, recurrence, metastasis and disease status. The samples included 39 (70.9%) males and 16 (29.1%) females with an average age of 58.9 years old (range: 25-88 years old).…”
Section: Chordoma Sample Collection and Tissue Microarraymentioning
confidence: 99%
“…The tissue microarray (TMA) was constructed from 55 individual chordoma patient specimens within a formalin-fixed paraffin-embedded (FFPE) block as previously described. 23,24 The clinicopathological characteristics of the specimens were collected and are outlined in Table 1, including age, gender, tumour location, recurrence, metastasis and disease status. The samples included 39 (70.9%) males and 16 (29.1%) females with an average age of 58.9 years old (range: 25-88 years old).…”
Section: Chordoma Sample Collection and Tissue Microarraymentioning
confidence: 99%
“…Gene therapy (GT), which uses nucleic acids to treat tumors, is considered a promising therapeutic strategy. In particular, small-interfering RNAs (siRNAs) have attracted great attention as potential therapeutic agents, because they can regulate protein expression by silencing mRNA (mRNA). , Despite the treatment potential of siRNAs, they have notable limitations, such as fast enzymatic degradation and low intracellular uptake rate in vivo , which necessitate the improvement in delivery to the target. In addition, RNA, owing to its strong negative charge, faces an electrostatic barrier against internalization by cells, which further hinders its therapeutic efficacy in vivo . Therefore, the combination of GT with other therapeutic methods is considered necessary to compensate for its inherent disadvantages.…”
mentioning
confidence: 99%
“…As for caspase-8, the prognostic/predictive value of CDK9, however, still remains controversial among different tumor types. Whereas some authors have indicated that high levels of CDK9 expression in patients with pancreatic adenocarcinoma are associated with significantly shortened OS, especially in well differentiated tumors [ 36 , 41 , 42 ], others have demonstrated that higher CDK9 expression is associated with significantly improved survival [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%